A cooperative solution for the three nation problem of exploitation of the southern bluefin tuna - Krawczyk, Jacek; Tolwinski, Boleslaw (School of Management Working Papers, 1992)
This paper is concerned with the problem of management of fisheries of the Southern Bluefin Tuna ( SBT). The problem involves three countries exploiting the fisheries, namely Australia, Ja pan, and New Zealand. Each country faces different economic conditions and may pursue different policies concerning their fishing efforts, catch quotas, etc., to achieve their specific goals. To avoid overexploitation of the fisheries, the three countries set up a Trilateral Commission that provides framework for negotiations on catch quotas. The ultimate goal of this study is to help to provide answers what the level of quotas should be. As a first step in that direction we consider a solution that maximizes the sum of benefit functions of the parties involved. In particular, we report that higher SBT quotas than the current ones can be allocated to the interested parties provided that the stock has achieved a better demographic structure, which consists of having more older fish than at present.